Non-symbiotic Seed Germination and In vitro Plant Development of Pholidota articulata - Prasad, R. Devendra; Pradan, Shreeti; Poudel, Mukti Ram; Pant, Bijaya (Nepalese Horticulture, 2021)
Pholidota articulata is an epiphytic orchid mostly used in ornamental cut/pot flower and in traditional medicine. As it has high ornamental and medicinal values, its population from natural habitats is decreasing, therefore, it is listed in the Appendix-II of Convention on International Trade in Endangered Species (CITES). The objective of the present study is to obtain the in vitro plants of P. articulata from seed culture to conserve its germplasm. The in vitro seed germination was carried out in different strengths of Murashige and Skoog (MS) and Knudson C (KnC) medium supplemented with various plant hormones. On the half-strength of MS medium, seeds were started to germinate after 4 weeks of primary culture and they were developed into protocorms with first leaf primordium earlier than on the other medium. Therefore, in vitro developed protocorms were sub-cultured on the half-strength of MS medium supplemented with different concentrations of 6-benzylaminopurine (BAP), gibberellic acid (GA3) and α-naphtalene acetic acid (NAA). They were successfully developed into shoots on the 1.5 mg/l BAP supplemented half-strength of MS medium. Later, they were inoculated on the half-strength of MS medium supplemented with different concentration of α-napthalene acetic acid (NAA), indole-3-acetic acid (IAA) and indole-3-butyric acid (IBA) for the root formation, where IBA supplemented medium was found effective for the development of roots. Thus, this study provides a reliable protocol for non-symbiotic seed germination and plant production, and reveals that seed-derived protocorms are good explants for the in vitro mass propagation for conservation and sustainable utilization in horticulture.